Integrasi Kearifan Lokal sebagai Sumber Belajar dalam Pembelajaran IPA melalui Pengembangan Media Digital - Ratna Hima Taftiana; Diaz Rhamadani; Alya Dina Ariyanto; Insih Wilujeng (Universitas Garut, 2026)
Integration of Local Wisdom as a Learning Resource in Science Learning through Digital Media Development. This study aims to summarize and analyze the development trends of science learning media based on local wisdom as an effort to improve the quality of meaningful learning in elementary and secondary schools. The method used is a literature review with a descriptive qualitative approach to scientific articles published in journals from 2020-2025 that develop learning videos as a support in the learning process. Media characteristics, implementation procedures, and effectiveness on student learning abilities are identified through the analysis stages carried out during the literature review process. The results of the study indicate that media based on local wisdom can improve creativity, conceptual understanding, critical thinking skills, and students' desire to learn. In addition, the application of this method has been proven to strengthen the relevance of science material because it explains scientific phenomena with community cultural practices, which makes learning more contextual. The final results of this study found that the development of videos and multimedia based on local wisdom makes a significant contribution to science learning in the 21st century. It can also be used as a reference for open innovation media in various regional community contexts. This study aims to summarize and analyze the development trends of science learning media based on local wisdom as an effort to improve the quality of meaningful learning in elementary and secondary schools. The method used is a literature review with a descriptive qualitative approach to scientific articles published in journals from 2020-2025 that develop learning videos as a support in the learning process. Media characteristics, implementation procedures, and effectiveness on student learning abilities are identified through the analysis stages carried out during the literature review process. The results of the study indicate that media based on local wisdom can improve creativity, conceptual understanding, critical thinking skills, and students' desire to learn. In addition, the application of this method has been proven to strengthen the relevance of science material because it explains scientific phenomena with community cultural practices, which makes learning more contextual. The final results of this study found that the development of videos and multimedia based on local wisdom makes a significant contribution to science learning in the 21st century. It can also be used as a reference for open innovation media in various regional community contexts.Keywords: Digital media, local wisdom, science learning